Associations between Oxidative/Nitrosative Stress and Thyroid Hormones in Pregnant Women-Tainan Birth Cohort Study (TBCS) - Po-Keng Cheng; Hsin-Chang Chen; Pao-Lin Kuo; Jung-Wei Chang; Wan-Ting Chang; Po-Chin Huang (MDPI AG, 2022)
Oxidative and nitrosative stress have been linked to thyroid function in both animal and human studies. In the present study, the associations between oxidative and nitrosative stress and thyroid hormones were investigated. Measurements were obtained from 97 Taiwanese pregnant women at the first, second, and third trimesters. Levels of five oxidative and nitrosative stress biomarkers (8-hydroxy-2'-deoxyguanosine [8-OHdG], 8-nitroguanine [8-NO2Gua], 4-hydroxy-2-nonenal-mercapturic acid [HNE-MA], 8-isoprostaglandin F2α [8-isoPGF2α], and malondialdehyde [MDA]) were measured using urine samples, and levels of five thyroid hormones (triiodothyronine [T3], thyroxine [T4], free T4, thyroid-stimulating hormone [TSH], and T4-binding globulin [TBG]) were measured in blood samples. Multiple linear regressions and linear mixed-model regressions were conducted to determine the associations between oxidative or nitrosative stress biomarkers and thyroid hormones in pregnant women. We found that TSH was negatively and significantly associated with 8-NO2Gua (−14%, 95% CI [−26.9% to −1.1%]) and HNE-MA (−23%, 95% CI [−35.9% to −10.0%]) levels. However, T4 (3%, 95% CI [0.2%-5.8%]) and free T4 (4.3%, 95% CI [0.8%-7.8%]) levels were positively and significantly associated with 8-NO2Gua. The T4 to TBG and free T4 to TBG ratios were positively and significantly associated with 8-NO2Gua level (T4/TBG: 3.6%, 95% CI [0.5%-6.7%]; free T4/TBG: 5.6%, 95% CI [0.2%-11.1%]). However, the TSH to T4 ratio was negatively and significantly associated with 8-NO2Gua level (−17.3%, 95% CI [−30.4% to −4.3%]). The T3 to TSH ratio was positively and significantly associated with HNE-MA level (25.2%, 95% CI [11.2%-39.2%]). However, the TSH to T4 and TSH to free T4 ratios were negatively and significantly associated with HNE-MA level (TSH/T4: −21.2%, 95% CI [−34.5% to −7.8%] and TSH/free T4: −24.0%, 95% CI [−38.3% to −9.6%]). Our findings suggest that an imbalance of oxidative and nitrosative stress may alter thyroid hormone homeostasis during pregnancy. Disruption of the maternal thyroid homeostasis during pregnancy would affect embryonic and fetal development.